CHALLENGES AND EFFORTS TO CONTROL DEFORESTATION IN ACEH'S BORDER AREAS: A STUDY OF SUBULUSSALAM CITY - Shabariah; Muryali; Risna Dewi; Cut Sukmawati; Lisa Iryani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research is entitled Deforestation Control: A Study of Forest Areas in Subulussalam City, Aceh. The main problem in this research is the increasing deforestation that has an impact on ecosystem damage, reduced biodiversity, and threats to the sustainability of community life. Subulussalam City was chosen as the research location because it is the area with the second highest deforestation rate in Aceh, especially in the Leuser Ecosystem (KEL) area. Theoretically, this research is based on the perspective of public administration, public management, and command and control theory which emphasizes the importance of regulation, supervision, and law enforcement in natural resource management. The research method uses a descriptive qualitative approach with data collection techniques in the form of interviews, observation, and documentation of informants from the DLHK, NGOs, business actors, and local communities. The results of the study indicate that the mechanism for controlling deforestation in Subulussalam City is carried out through the prohibition of illegal logging, restrictions on logging permits, routine patrols, and the use of technology such as satellite imagery and smart patrols. Obstacles found include limited human resources, infrastructure, weak coordination between agencies, and minimal community participation. Furthermore, economic pressures on communities and the practice of land conversion to plantations have exacerbated the rate of deforestation. The conclusion of this study is that deforestation control in Subulussalam City is underway, but its effectiveness remains limited. Institutional strengthening, increased technology-based monitoring, consistent law enforcement, and community empowerment are needed to maintain sustainable forest conservation.